Implementation of the Think Pair Share Model in Increasing Awareness of Diversity in Q.S. Al-Ḥujurāt/49:13 - Ridwan Aziz; Abur Hamdi Usman (FITK UIN Walisongo Semarang, 2025)
The low level of students' understanding of the values ​​of diversity in Islamic teachings, particularly in Q.S. Al-Hujurāt/49:13, encourages the need for learning strategies that can facilitate conceptual understanding while strengthening social attitudes. This study aims to analyze efforts to improve the understanding of fourth-grade students of Sumurboto Public Elementary School through the implementation of the Think-Pair-Share (TPS) cooperative learning model. This study uses a Classroom Action Research (CAR) approach which is implemented in three cycles, each including the planning, implementation, observation, and reflection stages. The research subjects were 26 students (9 boys and 17 girls). Data collection was carried out through learning outcome tests, participatory observations, and interviews, with qualitative and quantitative descriptive data analysis. The results of the study showed a significant increase in students' understanding: the percentage of learning completion increased from 55% (cycle I), 75% (cycle II), to 90% in cycle III. The average score also increased from 74 on the pre-test to 88 on the post-test. Furthermore, students' social interactions and engagement in discussions increased, indicating that TPS was effective in fostering collaboration and connecting diversity values ​​to real-life contexts. These findings provide an original contribution to the application of cooperative models for teaching Islamic values ​​in elementary schools, while also enriching inclusive and contextual pedagogical practices